Analyzing the Reasons of Occupational Health and Safety Training Students’ Profession Choice: A Research at Pamukkale University – Honaz Vocational School - Arpat, Bulent; Yesil, Yeliz (European Scientific Journal, ESJ, 2017)
If individuals choose the correct profession for them they will be motivated too much, they will get a better carrier and will obtain more qualified and efficient job. The chosen profession should provide salary and in addition to this the individuals can be satisfied with their profession, so it is important for the students to choose the correct profession. The purpose of this research is to analyze the reasons of occupational health and safety training students’ profession choice at Pamukkale University-Honaz Vocational School. 5 Likert Scale is used in the research and the data are analyzed by SPSS. In this research in the first part, the profession definition and the factors that influence profession choice are given, in the second part the importance of choosing the correct profession, in the third part method, methodology and findings are given.